APPLICATION OF SQ3R ON THE SUCCESS OF THE "ROLE PLAY" METHOD IN "ENGLISH FOR SPECIFIC PURPOSE" COURSE, ADMINISTRATIVE STUDY PROGRAM, STIA BANTEN, PANDEGLANG, BANTEN - Hendra Hendra (Journal of English Language Teaching and Literature (JELTL), 2020)
SQ3R is a method to get knowledge from reading sources. Thus, the contents of a reading source will become effective as a knowledge, in this case the knowledge instructed by the lecturer in the "English for Specific Purpose" Course. The desired knowledge obtained is the knowledge of "ISO" (International Organization for Stadardization) . After getting the contents of a reading about the "ISO", the lecturer will form a group for a conversation simulation in a company meeting by using the "Role Play" method, where students in the group will act as managers in a company. The limitation of this research is to only focus on the role of the SQ3R method on the "Role Play" method as one of the methods for teaching students' Speaking Skills at STIA Banten, especially students of the "English for Specific Purpose" class. In conducting this research, the author used the Action Research method or take certain actions or treatments to see the success of students to be able to communicate. Then, the data used is observation data with recording techniques and also the value of student learning outcomes. The results achieved in this study are that there is a close relationship between SQ3R conducted by students to find out about "ISO" and then practice it in the classroom using the "Role Play" method. From the results obtained by students, there is also visible progress before using the SQ3R method with students' speaking ability after using the SQ3R method.